Alternative splicing of papilin and the diversity of Drosophila extracellular matrix during embryonic morphogenesis. - Kramerova, I.A.; Kramerov, A.A.; Fessler, J.H. (Developmental Dynamics, 2003)
Papilins are extracellular matrix proteins that share a particular, common order of types of protein domains. They occur widely, from nematodes to man, and can differ in the number of repeats of a given type of domain. Protein variety is increased by differential splicing of pre-mRNA. We report that Drosophila, which has a compact genome, expresses three splice variants of papilin during embryogenesis in developmentally defined patterns. These isoforms have different numbers of Kunitz and IgC2 domains. The papilin isoforms are expressed in specific cell types and contribute to different extracellular matrices in gastrulation folds, early mesoderm, heart formation, basement membranes, and elaboration of the excorporeal peritrophic membrane that lines the gut. This finding indicates an unexpectedly broad spectrum of different pericellular matrices in Drosophila embryos. Such papilin-containing matrices have developmental as well as functional significance, as we previously showed that both suppression of papilin synthesis and ectopic overexpression lethally disrupt organogenesis.